Synthesis and Characterisation of Hydroxyl-terminated Liquid Natural Rubber by Photo-Fenton Reaction - H. L. Pham; B. T. Do; T. S. Pham; D. G. Le (ASEAN Journal on Science and Technology for Development, 2013)
Hydroxyl-terminated liquid natural rubber (HTNR) was prepared by the photo-Fenton reaction, which was carried out in solution in the presence of H2O2/Fe(II) combined with UV irradiation. The HTNR obtained was characterized by GPC, FT-IR, 1H-NMR, 13C-NMR, DEPT-NMR spectroscopy as well as by chemical methods. A probable mechanism leading to the formation of HTNR was discussed based on the analytical data.